Assessing Frequency Ratio Method for Soil Erosion Susceptibility Map in Cameron Highlands, Malaysia - Bin Mohamad Nor , Muhammad Fadhil (Universiti Teknologi PETRONAS, 2018)
Cameron Highlands, which have the area covered of 712 km2 is one of the district of Pahang state in peninsular Malaysia. This place also very famous among the people as the tourism spot because of the hilly terrain that promote nice view and cool weather. However, soil erosion is become one of the main issues and problems, due to the heavy rains and activities of the community. This study is to produce soil erosion susceptibility map in Cameron Highlands, using frequency ratio (FR) model integrated with Geographic Information System. Four thematic layers, consisting of elevation, slope, aspect, and curvature, were used in the susceptibility analysis. 140 locations of soil erosion was used as the data obtain from previous studies. Four causative factors maps produced with the aids of ArcGIS software. The weighted values for each factor were calculated according to frequency ratio model and soil erosion susceptibility map was created. Finally, three zone includes low, moderate and high was shown in the map. Approximately 51 % of the map show the area that have low prone soil erosion to occur. While, 40% of the area show zone of moderate prone to soil erosion. The area that fall under zone of high was about 19% of the total area. In order to validate the performance and accuracy of the model, area under the curve (AUC) technique was used. Based on the validate technique, the success rate shown that Frequency Ratio model had 74.42 % performance. While, the prediction rate of the model shown accuracy of 74.26 %. As the conclusion, this result shows that the Frequency Ratio model had successful performance.